Peta Persebaran Kasus Diare Menurut Kepadatan Penduduk di Provinsi Bali Tahun 2020-2022 - Ainiyah Hasna Fadhilah (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Bali Province has a high population density, which has the potential to affect the distribution of infectious diseases such as diarrhea. However, mapping the distribution of diarrhea cases based on population density is still limited and does not meet good cartographic principles. Therefore, this study aims to present data on the distribution of diarrhea cases based on population density in Bali Province during the 2020-2022 period. This study used an analytic observational method with a cross-sectional design. The data used were secondary data from the Bali Province Health Profile and the Central Statistics Agency (BPS) for 2020-2022. Data analysis was carried out using geographic mapping with Geographic Information Systems (GIS) and statistical tests in the form of multiple linear regression and Spearman correlation. The results showed an increase in the strength of the relationship between population density and the number of diarrhea cases, as indicated by the rho value which increased from 0.1833 in 2020 to 0.6000 in 2022. However, this relationship was not statistically significant (p-value > 0.05), indicating that population density is not the only factor contributing to the increase in diarrhea cases. Other factors such as sanitation, access to clean water, and public awareness in maintaining hygiene also play a role in the spread of this disease. Although there is a trend that an increase in population density in Bali goes hand in hand with an increase in diarrhea cases, this relationship is not statistically strong enough. Therefore, a multidisciplinary approach is needed to address diarrhea cases, including improved sanitation facilities, public health education, as well as strengthening the spatial data-based disease monitoring system.